Sulindac solid dispersions: development, characterization and in vivo evaluation of ulcerogenic activity in rats - Yusuf A. Haggag, Sanaa A. El-Gizawy, Esmat E. Zein El-din, Nagla A. El-Shitany, Mohamed A. Osman (Journal of Applied Pharmaceutical Science, 2016)
Sulindac is a poorly soluble nonsteroidal anti-inflammatory drug associated with gastrointestinal intolerance as its serious side effect. This work investigated the ability of Eudragit Ll00-55 (Eud L100-55), Cellulose acetate phthalate (CAP) and β-cyclodextrin (β-CD) to ameliorate its gastric ulcers induced in rats. Binary solid dispersions (SD) using solvent evaporation method were fabricated for the drug with different drug to polymer weight ratios of 1:1, 1:2 and 1:3. SD and physical mixture were characterized through in vitro dissolution, infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and scanning electron microscopy. The best enteric SD and SD using β-CD was tested in vivo for their ulcerogenic activity. Sulindac was highly dispersed inside CAP system that efficiently limited its release inside the stomach while no occurrence of any physicochemical interactions with the drug. β-CD improved the drug aqueous solubility, however it couldn’t protect against gastric ulcers induced by sulindac. SD using CAP as enteric polymer at a ratio of 1:2 significantly suppressed gastric ulceration. Direct exposure of sulindac to the stomach wall had the major contribution to its ulcerogenic activity rather than its poor gastric solubility. The gastrointestinal intolerance of sulindac could be addressed by avoiding its acute local contact with the ulcer-prone areas.
Keywords: Sulindac, binary solid dispersion, enteric polymers, &beta; -cyclodextrin, acute local contact, gastric ulcer.